Horizontal Ridge Augmentation using GBR with a Native Collagen Membrane and 1:1 Ratio of Particulated Xenograft and Autologous Bone: A 1‐Year Prospective Clinical Study. (9th June 2016) - Meloni, Silvio Mario; Jovanovic, Sascha A; Urban, Istvan; Canullo, Luigi; Pisano, Milena; Tallarico, Marco
Abstract: Aim: To clinically and radiographically evaluate bone regeneration of severe horizontal bone defects. Materials and Methods: This study was designed as a single cohort, prospective clinical trial. Partially or fully edentulous patients, having less then 4 mm of residual horizontal bone width were selected and consecutively treated with resorbable collagen membranes and a 1:1 mixture of particulated anorganic bovine bone and autogenous bone, 7 months before implant placement. Tapered body implants were inserted and loaded 3 to 6 months later with a screw retained crown or bridge. Outcomes were: implant survival rate, any biological and prosthetic complications, horizontal alveolar bone dimensional changes measured on cone beam computed tomography (CBCT) taken at baseline and at implant insertion, peri‐implant marginal bone level changes measured on periapical radiographs, plaque index (PI), and bleeding on probing index (BoP). Results: Eighteen consecutive patients (11 females, 7 males) with a mean age of 56.8 years (range 24–78) and 22 treated sites received 55 regular platform implants. No patient dropped‐out and no implants failed during the entire follow‐up, resulting in a cumulative implant survival rate of 100%. No prosthetic or biological complications were recorded. Supraimposition of pre‐ and 7‐month post‐operative CBCT scans revealed an average horizontal bone gain of 5.03 ± 2.15 mm (95% CI: 4.13–5.92 mm). One year after final prosthesis delivery, mean marginal bone loss was 1.03 ± 0.21 mm (95% CI 0.83–1.17 mm). PI was 11.1% and BoP was 5.6%. Conclusion: Within the limitation of the present study, high implant survival rate and high average bone augmentation seem to validate the use of collagen resorbable membranes with a 1:1 mixture of particulated anorganic bovine bone and autogenous bone, for the reconstruction of severe horizontal ridge defects.